Ocean heat uptake prevents polar climate reversibility in HadGEM3-GC3.1-LL climate model - Jeff Ridley; Mark Ringer; Ed Blockley (Climatic Change, 2026)
The reversibility of climate change has seen much discussion – in particular through consideration of scenarios that overshoot a warming target before being cooled through carbon sequestration. The uptake of heat into the deep ocean during warming can result in a lag in the response of global and local climate when warming is reversed. The impact of ocean heat uptake on climate reversibility can be efficiently investigated using an idealised abrupt transition from pre-industrial atmospheric CO 2 concentrations to four times pre-industrial levels followed by an abrupt transition back to pre-industrial levels. New multi-centennial simulations are undertaken, using the HadGEM3-GC3.1-LL climate model, in which abrupt transitions to pre-industrial conditions are simulated after 25, 100, 250 and 1000 years from the start of the existing instantaneous abrupt-4xCO2 CMIP6 experiment. These simulations result in an increasing amount of heat being input to the ocean, which is subsequently released during the cooling phase. We show that the loss of heat from the ocean in the cooling phase is slower than the heat uptake during warming, with the climate, on a multi-centennial timescale, tending towards a warmer state than the pre-industrial control. During the warm state, the Arctic undergoes Atlantification and, after the cooling phase, returns to a quasi-equilibrium state with greater poleward transport of Atlantic water. The Southern Ocean becomes more isolated from the global system during warming and takes up considerable local heat, which is vented through sustained deep convection during cooling. In neither polar region does the sea ice return to its pre-industrial state, and thus we find that the climate system is not readily reversible for high warming levels. This will have implications for climate overshoot in the real world if warming is not controlled.

Investigating physical constraints on climate feedbacks using a perturbed parameter ensemble - Yoko Tsushima; Mark A. Ringer; Gill M. Martin; John W. Rostron; David M. H. Sexton (Climate Dynamics, 2020)

The impact of performance filtering on climate feedbacks in a perturbed parameter ensemble - John W. Rostron; David M. H. Sexton; Carol F. McSweeney; Kuniko Yamazaki; Timothy Andrews; Kalli Furtado; Mark A. Ringer; Yoko Tsushima (Climate Dynamics, 2020)
A key contribution to the latest generation of climate projections for the UK (UKCP18) was a perturbed parameter ensemble (PPE) of global coupled models based on HadGEM3-GC3.05. Together with 13 CMIP5 simulations, this PPE provides users with a dataset that samples modelling uncertainty and is ideal for use in impacts studies. Evaluations of global mean surface temperatures for this PPE have shown twenty-first century warming rates consistently at the top end of the CMIP5 range. Here we investigate one potential contributory factor to this lack of spread: that the methodology to select plausible members from a larger, related PPE of atmosphere-only experiments preferentially ruled out those predicted to have more negative climate feedbacks (i.e. lower climate sensitivities). We confirm that this is indeed the case. We show that performance in extratropical long-wave cloud forcing played a key role in this by constraining ice cloud parameters, which in turn constrained the feedback distribution (though causal links are not established). The relatively weak relationship driving this constraint is shown to arise from stronger relationships for the long-wave and short-wave cloud feedback components, which largely cancel out due to changes in tropical high clouds. Moreover, we show that the strength of these constraints is due to a structural bias in extratropical long-wave cloud forcing across the PPE. We discuss how choices made in the methodology to pick the plausible PPE members may result in an overly strong constraint when there is a structural bias and possible improvements to this methodology for the future.

Seasonally variant low cloud adjustment over cool oceans - Youichi Kamae; Robin Chadwick; Duncan Ackerley; Mark Ringer; Tomoo Ogura (Climate Dynamics, 2019)

Robustness, uncertainties, and emergent constraints in the radiative responses of stratocumulus cloud regimes to future warming - Yoko Tsushima; Mark A. Ringer; Tsuyoshi Koshiro; Hideaki Kawai; Romain Roehrig; Jason Cole; Masahiro Watanabe; Tokuta Yokohata; Alejandro Bodas-Salcedo; Keith D. Williams; Mark J. Webb (Climate Dynamics, 2016)

Quantitative evaluation of the seasonal variations in climate model cloud regimes - Yoko Tsushima; Mark A. Ringer; Mark J. Webb; Keith D. Williams (Climate Dynamics, 2013)

A step-response approach for predicting and understanding non-linear precipitation changes - Peter Good; William Ingram; F. Hugo Lambert; Jason A. Lowe; Jonathan M. Gregory; Mark J. Webb; Mark A. Ringer; Peili Wu (Climate Dynamics, 2012)

Climate forcings and climate sensitivities diagnosed from atmospheric global circulation models - Bruce T. Anderson; Jeff R. Knight; Mark A. Ringer; Clara Deser; Adam S. Phillips; Jin-Ho Yoon; Annalisa Cherchi (Climate Dynamics, 2010)

(−)-Menthol biosynthesis and molecular genetics - Rodney B. Croteau; Edward M. Davis; Kerry L. Ringer; Mark R. Wildung (The Science of Nature, 2005)

Interannual variabilty of the earth’s radiation budget: some regional studies - Mark A. Ringer (International Journal of Climatology, 1997)

Interannual variabilty of the earth's radiation budget: some regional studies - Mark A. Ringer (International Journal of Climatology, 1997)